Gyrokinetic study of transport suppression in JET plasmas with MeV-ions and toroidal Alfvén eigenmodes. (27th September 2022) - Mazzi, S; Garcia, J; Zarzoso, D; Kazakov, Ye O; Ongena, J; Dreval, M; Nocente, M; Štancar, Ž; Szepesi, G; ,
Abstract: The impact of fast ions, generated in the MeV-range through the efficient application of the three-ion scheme in JET plasmas, on the turbulence properties is presented through complex numerical simulations. The suppression of the ion-scale turbulent transport is studied by means of in-depth gyrokinetic numerical analyses. Such a suppression is demonstrated to be achieved in the presence of toroidal Alfvén eigenmodes (TAEs) destabilized by the highly energetic ions. Details on the TAE excitation are also provided with a multi-code analysis. The inherently nonlinear and multi-scale mechanism triggered by the fast ions, also involving the high-frequency modes and the large-scale zonal flows, is deeply analyzed. Such mechanism is thus demonstrated, with experimental validating studies, to be the main cause of turbulence suppression and improvement of ion thermal confinement. Additional simulations address the implications of reversed shear magnetic equilibrium on the turbulent transport.